Molecular phylogeny of atractus (Serpentes, dipsadidae), with emphasis on Ecuadorian species and the description of three new taxa - Arteaga, Alejando (2017)
We present a molecular phylogeny of snake genus Atractus, with an improved taxon sampling that includes 30 of the 140 species currently recognized. The phylogenetic tree supports the existence of at least three new species in the Pacific lowlands and adjacent Andean slopes of the Ecuadorian Andes, which we describe here. A unique combination of molecular, meristic and color pattern characters support the validity of the new species. With the newly acquired data, we propose and define the A. iridescens species group, as well as redefine the A. roulei species group. The species A. iridescens is reported for the first time in Ecuador, whereas A. bocourti and A. medusa are removed from the herpetofauna of this country. We provide the first photographic vouchers of live specimens for A. multicinctus, A. paucidens and A. touzeti, along with photographs of 19 other Ecuadorian Atractus species. The current status of A. occidentalis and A. paucidens is maintained based on the discovery of new material referable to these species. With these changes, the species number reported in Ecuador increases to 27, a number that is likely to increase as material not examined in this work becomes available and included in systematic studies. © Alejandro Arteaga et al.